1970
DOI: 10.2134/agronj1970.00021962006200050028x
|View full text |Cite
|
Sign up to set email alerts
|

Semidwarf Winter Wheat Response to Early Spring Clipping and Grazing1

Abstract: Vegetation removal in early spring by clipping or by grazing was studied in six fields of semidwarf winter wheat (Triticum aestivum L.). Varieties grown were ‘Games’ or ‘Nugaines’ which are common soft white wheat having exceptional stooling and yielding ability. Grazing was started as soon as livestock could obtain adequate feed from the early spring growth and stopped prior to the time the upper node could be removed by grazing. Clipping treatments were applied during this period. Removing vegetation either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
2

Year Published

1987
1987
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 3 publications
(3 reference statements)
3
20
0
2
Order By: Relevance
“…Francia et al (2006) reported a 13.5% grain yield reduction for barley after forage removal in southern Italy. Higher degrees of reduction have also been reported (Dann et al, 1983;Pumphrey, 1970). As reviewed by Harrison et al (2012), postdefoliation yield reduction may happen due to several factors, such as frost damage after defoliation, poor leaf area development, delayed maturation, increased rates of green area senescence, and decreased grain filling period.…”
Section: Discussionmentioning
confidence: 92%
“…Francia et al (2006) reported a 13.5% grain yield reduction for barley after forage removal in southern Italy. Higher degrees of reduction have also been reported (Dann et al, 1983;Pumphrey, 1970). As reviewed by Harrison et al (2012), postdefoliation yield reduction may happen due to several factors, such as frost damage after defoliation, poor leaf area development, delayed maturation, increased rates of green area senescence, and decreased grain filling period.…”
Section: Discussionmentioning
confidence: 92%
“…Delay of clipping at growing season reduce cereal grain yield [8]. It is due to reduction of leaf area, photosynthetic rate and consequently decreases in 1000-kernel weight and spike per square meter [9].…”
Section: Resultsmentioning
confidence: 99%
“…With delaying clipping vegetative growth reduced and consequently dwarfed plant height. Researchers stated that clipping at different stages of growth in cereal such as wheat and barley reduce 10% plant height [9] [13].…”
Section: Resultsmentioning
confidence: 99%
“…Os resultados obtidos neste experimento, indicando acréscimo significativo no teor de proteína bruta dos grãos pelos cortes, na média dos cereais, não correspondem claramente aos de Pumphrey (1970 Os teores de fibra bruta dos genótipos analisados não foram afetados (p>0,05) pelos cortes (Tabela 2).…”
Section: Resultsunclassified
“…Estudando o efeito de cortes e de pastejo em trigos de inverno nos Estados Unidos, Pumphrey (1970) observou que o corte no início da primavera não teve efeito consistente no conteúdo de proteína do grão. O conteúdo médio de proteína no grão aumentou levemente em quatro experimentos, e em outros dois experimentos o conteúdo protéico pareceu decrescer com a remoção de vegetação pelos cortes.…”
Section: Introductionunclassified